Dampak Dampak Pengambilan Keputusan Kepala Sekolah Bagi Peningkatan Mutu Pendidikan - Afentis Nehe; Wasitohadi Wasitohadi; Marinu Waruwu (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2023)
This study aims to determine the impact of the principal's decision-making on improving the quality of education at SMP Negeri 3 Gunungsitoli Selatan. To achieve this goal, the researchers used data collection techniques through interviews, observation, and documentation. Students and teachers are the source of the research and the data is processed using a qualitative descriptive analysis to determine the impact of the Principal's Decision Making on improving the quality of Education at SMP Negeri 3 Gunungsitoli Selatan. The results of the study show that: (1) The impact of the Principal's Decision Making at SMP Negeri 3 Gunungsitoli Selatan shows very significant results (2) Students at SMP Negeri 3 Gunungsitoli Selatan are very responsive and able to improve student achievement (3) The Impact of Influence on the Decision Making of the Principal towards teachers at SMP Negeri 3 Gunungsitoli Selatan is very strong and shows positive results for the teaching and learning process at school.